Aplikasi Konsep Eco-Culture dalam Pengembangan Kampung Wisata Buah Baran Bercahaya - Titisari, Ema; Azizah, Siti; Kurniawan, Syahrul; Ridjal, Abraham M; Yuniarti, Rahmi (RUAS, 2022)
The concept of eco-culture has a sustainability paradigm that emphasizes the harmony of humans and ecosystems. The target is the strengthening of local characters through the study of local genius, as well as the application of science and technological innovation in managing the potential for improving the quality of the environment and humans. Increasing the economy through tourism is its added value. Kampung Baran has a unique ethnographic and geographical setting inhabited mostly by low-income people. The potential that can be developed is agriculture which is now slowly starting to be abandoned. This study examines the application of the eco-culture concept which consists of an image of space, an image of building, and an idealized concept of place for the development of Kampung Baran. Through a descriptive-phenomenological study, the researcher explores the physical-spatial-architectural and economic-social-cultural phenomena of Kampung Baran as the object of study. Furthermore, the study of the application of the concept of eco-culture in the village of Baran was carried out through a SWOT analysis. The results obtained indicate that the concept of eco-culture can be applied in Kampung Baran by emphasizing on strengthening the noble values of the culture of agrarian communities in the expression of tangible and intangible heritage that is adaptive to cultural dynamics and strengthening and developing local potential.